Fitz-Hugh-Curtis Syndrome: A Comprehensive Review - Kumari, Santosh; Kaur, Jasbir; Sheoran, Poonam; Sharma, Shaweta (International Journal of Nursing Research, 2023)
Fitz-Hugh-Curtis syndrome (FHCS) is a rare disorder that occurs in women. FHCS is a chronic manifestation of pelvic inflammatory disease (PID). It is characterized by inflammation of the membrane lining the stomach (peritoneum) and the tissues surrounding the liver (perihepatitis). The majority of cases occur in women of reproductive age between 15 and 30 years of age who have PID. Approximately 4–14% of women with PIDs develop FHCS. It occurs with greater frequency in adolescents with PIDs because they are more susceptible to infection. In extremely rare cases, it has occurred in men. PIDs are an ascending microbial infection involving the genital tract that affects sexually active. The United States experiences 750,000 cases of PID each year. FHCS is an uncommon manifestation of PIDs involving around 4% of adolescents. According to a case report, a 23-year-old girl found with FHCS at Bombay Hospital and Institute of Medical Sciences, Mumbai, Maharashtra, India. Many organisms are associated with FHCS, Chlamydia trachomatis is the most common pathogen involved. Common symptoms include severe pain in the upper right area (quadrant) of the abdomen, fever, chills, headaches, and a general feeling of poor health (malaise). There are insufficient data documenting the prognosis of FHCS as it usually responds to antibiotics very well. In one trial of triple therapy (penicillin-gentamicin-metronidazole) versus Augmentin for non-chlamydial salpingitis, only one patient in each treatment group had treatment failure.